Population consequences of male selection at birth when the sex probabilities can be altered - Frank T. Denton; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2013)
We explore the implications of male preference stopping rules for a stable population, and more generally the aggregate implications of higher male/female birth ratios. We begin by specifying nine alternative family stopping rules, derive their probability functions, and simulate the long-run effects on population growth rates and age and sex ratios. We then move away from the idea of explicit stopping rules and simulate the population effects of 81 alternative combinations of birth sex ratios and fertility rates under (implicit) preference for male children. The results show how male preference and fertility choices at the individual family level can affect the overall characteristics of a population.
Keywords: J12; J13; C63; 330; Male preference; Sex selection; Stopping rules; Population effects